2022
DOI: 10.3390/ijerph19159273
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Hospital Anxiety and Depression Scale (HADS) in Previously Hospitalized COVID-19 Patients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus is associated with psychological/emotional disturbances. This study aimed to assess internal consistency, reliability, and construct validity of the Hospital Anxiety and Depressive Scale (HADS), as a patient-reported outcome measure (PROM) for evaluating emotional consequences of SARS-CoV-2 in hospitalized COVID-19 survivors with long COVID. The LONG-COVID-EXP-CM is a multicenter cohort study including patients hospitalized by COVID-19 during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“… 18 Both the HADS anxiety (HADS-A; 7 items; range, 0-21 points) and HADS depressive (HADS-D; 7 items; range, 0-21 points) scales were used. 19 A cutoff score of 12 points or more for the HADS-A was indicative of anxiety symptoms, and a cutoff score of 10 points or more for the HADS-D was indicative of depressive symptoms. 20 The PSQI (range, 0-21 points) was used to assess sleep quality during the previous month, in which a cutoff of 8.0 points or more was considered indicative of poor sleep quality.…”
Section: Methodsmentioning
confidence: 99%
“… 18 Both the HADS anxiety (HADS-A; 7 items; range, 0-21 points) and HADS depressive (HADS-D; 7 items; range, 0-21 points) scales were used. 19 A cutoff score of 12 points or more for the HADS-A was indicative of anxiety symptoms, and a cutoff score of 10 points or more for the HADS-D was indicative of depressive symptoms. 20 The PSQI (range, 0-21 points) was used to assess sleep quality during the previous month, in which a cutoff of 8.0 points or more was considered indicative of poor sleep quality.…”
Section: Methodsmentioning
confidence: 99%
“…Anxiety and depressive symptoms were assessed with the Hospital Anxiety and Depression Scale (HADS) [ 40 ]. Each scale includes 7 items evaluating anxiety (HADS-A) or depressive (HADS-D) symptoms on a 4-point Likert scale (0–3).…”
Section: Methodsmentioning
confidence: 99%
“…The score of each subscale ranges from 0 to 21 points, where ≥12 points on the HADS-A are indicative of anxiety symptoms and ≥10 points on the HADS-D indicate of depressive symptoms [ 41 ]. A recent study has revealed that both scales of the HADS exhibit good internal consistency in people with the post-COVID-19 condition [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been used owing to the fact that it has proven to be psychometric valid and reliable which makes it a useful and easily applicable tool to screen for anxiety and depression in clinical practice [ 21 25 ].…”
Section: Methodsmentioning
confidence: 99%